2015
DOI: 10.1111/aogs.12681
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for pregnancy‐related lumbopelvic pain: a systematic review of physiotherapy modalities

Abstract: The levels of evidence were strong for a positive effect of acupuncture and pelvic belts, but weak for an effect of specific exercises. Caution should prevail in choosing other interventions for pregnancy-related lumbopelvic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(149 citation statements)
references
References 86 publications
(171 reference statements)
6
128
0
11
Order By: Relevance
“…Richards et al (15) and Gutke et al (17) -although having found some evidence that physical therapy through exercises, acupuncture and pelvic support belts, among others, could have positive effects on pregnancy low back and pelvic pain -could not could perform a meta-analysis due to the heterogeneity of the studies included in their systematic review. Gutke et al (17) found in a recent systematic review, a weak level of evidence of the effect of specific exercises guided by physical therapists even with different focuses and supervised by health professionals, are described as an importance resource for ensuring assistance during pregnancy, as it is also a space for sharing experiences, feelings and affects that are common to the period (48)(49)(50).…”
Section: Low Back And/or Pelvic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Richards et al (15) and Gutke et al (17) -although having found some evidence that physical therapy through exercises, acupuncture and pelvic support belts, among others, could have positive effects on pregnancy low back and pelvic pain -could not could perform a meta-analysis due to the heterogeneity of the studies included in their systematic review. Gutke et al (17) found in a recent systematic review, a weak level of evidence of the effect of specific exercises guided by physical therapists even with different focuses and supervised by health professionals, are described as an importance resource for ensuring assistance during pregnancy, as it is also a space for sharing experiences, feelings and affects that are common to the period (48)(49)(50).…”
Section: Low Back And/or Pelvic Painmentioning
confidence: 99%
“…Other reviews focused on the outcome of low back and pelvic pain, but did not restrict their approach to therapeutic exercises, guided or supervised by physical therapists, and/or included other types of treatment (14)(15)(16)(17)(18). But there are still few studies on the effects of physical therapy intervention with exercises on pregnancy low back and pelvic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Podobnie sytuacja przedstawia się odnośnie ćwiczeń w wodzie. W dostępnych doniesieniach [22] przyniosły one znaczącą redukcję intensywności odczuwanego bólu oraz mniejszy odsetek urlopów zdrowotnych wśród kobiet z LP jednakże nie zaobserwowano podobnych efektów w grupie z PGP. Ze względu na małą ilość randomizowanych badań kontrolowanych siła tych dowodów nie jest wystarczająca, aby móc bezsprzecznie stwierdzić o skuteczności tego rodzaju interwencji [21].…”
Section: Fizjoterapiaunclassified
“…This condition is more common among females and represents a trouble for women in the gestational period (1) . Considering that more than two-thirds of the pregnant women have LBP, this is considered the most common discomfort during pregnancy (1) and is often severe enough to interfere with daily life, reducing the ability to be active, causing limitations in the performance and productivity at work (2) . In a study carried out in Brazil, the prevalence of low back pain in pregnant women was high; 93.23% of the women reported pain (3) .…”
Section: Introductionmentioning
confidence: 99%
“…A therapy for the treatment of LBP during pregnancy is acupuncture, which seems to be effective in reducing symptoms and consequently improving the quality of life of pregnant women, and is able to alleviate pain when compared to usual care (1)(2) . Acupuncture is a traditional Chinese technique that aims to promote healing through the stimulation of body balance and the performance of negative and positive energies (5) .…”
Section: Introductionmentioning
confidence: 99%